2018
DOI: 10.3389/fpsyg.2018.01048
|View full text |Cite
|
Sign up to set email alerts
|

Social Facilitation of Laughter and Smiles in Preschool Children

Abstract: Surprisingly little is known about the social dimensions of laughter in preschool children. We studied children’s responses to amusing video clips in the presence or absence of peers. The sample consisted of 9 boys and 11 girls aged 31–49 months (M 39.8, SD 4.2) who watched three cartoons under three different conditions: individually, in pairs, or in groups of 6 or 8. The social viewing conditions showed significantly higher numbers of laughs and smiles than the individual viewing condition. On average childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 60 publications
(81 reference statements)
1
22
0
Order By: Relevance
“…As part of the Complexity and Continuity Hypothesis, we therefore argue that great ape laughter and their open-mouth faces of play are homologs of the two arguably strongest behavioral indicators of positive affect in humans, expressions that are both frequently and, to some extent, similarly found in young children's play (Rothbart, 1973 ; Addyman et al, 2018 ). Consequently, humans are not unique in producing laughter and smiles of positively grounded motivations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As part of the Complexity and Continuity Hypothesis, we therefore argue that great ape laughter and their open-mouth faces of play are homologs of the two arguably strongest behavioral indicators of positive affect in humans, expressions that are both frequently and, to some extent, similarly found in young children's play (Rothbart, 1973 ; Addyman et al, 2018 ). Consequently, humans are not unique in producing laughter and smiles of positively grounded motivations.…”
Section: Discussionmentioning
confidence: 91%
“…Play vocalizations and open-mouth faces can be found among primates early in their development (Tomonaga et al, 2004;Bard et al, 2014) and across their different populations (e.g., in chimpanzees: Matsusaka, 2004;Davila-Ross et al, 2011). Interestingly, the way playing great apes produce their multimodal and unimodal expressions of play strongly resembles the way playing children produce laughter and open-mouth smiles of positive affect (Rothbart, 1973;Addyman et al, 2018), respectively. Whereas, such basic observations might naturally lead to the notion of phylogenetic continuity from primordial play expressions to human laughter and smiles of positive affect (Darwin, 1872;Redican, 1982), other possible explanations are that laughter and smiles are human-unique behaviors or that they evolved from different primordial expressions (van Hooff, 1972;Preuschoft and van Hooff, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Two, laughter occurs primarily in social settings. Apes, children, and grownups are all more likely to laugh when near others than when alone (Addyman et al, 2018; Provine, 2001; Scott et al, 2014). Three, laughter is universally recognizable (G.…”
Section: General Discussion and Takeawaysmentioning
confidence: 99%
“…Multiple studies with adults have shown that for smiling and laughter to be expressed, social partnersand not humor, per se -are requisite (Panksepp, 2000;Provine, 2004;Scott, Lavan, Chen & McGettigan, 2014). LaFrance (2011) has even reported this effect in 10-montholds who were less likely to smile when alone than when in the presence of other people, and Addyman, Fogelquist, Levakova, and Rees (2018) reported the same effect in toddlers watching cartoons. When people are a central part of the context -as is the case in studies of humorous incongruity -the infant relates to the event differently because the presence of another being with the potential for evaluative reactions has opened up the infant's own potential reactions to the event, inviting emotional responses from the infant of a more typical kind -like laughter, for instance.…”
Section: Making Sense Of Incongruitymentioning
confidence: 99%